Diaminotriazinyl-Substituted N-Heterotriangulene: Hydrogen Bonding-Driven Self-Assembly in the Solid State, in the Gas Phase and on Surfaces - Borstelmann, Jan; Miguez Lago, Sandra; Geßner, David; Ammon, Maximilian Michael; Hitzenberger, Jakob; Hampel, Frank; Drewello, Thomas; Maier, Sabine; Kivala, Milan (Chemistry - A European Journal, 2025)
We report the synthesis and comprehensive characterization of a dimethylmethylene-bridged N-heterotriangulene (N-HTA) with diaminotriazinyl groups to guide the self-assembly through directional hydrogen bonding. Mass spectrometry collision-induced dissociation experiments indicated the formation of multiply charged clusters in the gas phase. Single crystal X-ray diffraction studies revealed that the solid state packing is governed by an interplay between the hydrogen bonding and the solvent system used for crystallization. The self-assembly on both semiconducting and insulating surfaces upon simple drop-casting was disclosed by atomic force microscopy and scanning tunneling microscopy. The strong hydrogen bonding leads to robust self-assembly on surfaces, which can be conveniently achieved by simple solution processing techniques under ambient conditions.
CRIS-Team Scopus Importer:2025-02-28
Keywords: hydrogen bonding; mass spectrometry; nitrogen-heterocycles; scanning probe microscopy; self-assembly

Tailored solution‐based N‐heterotriangulene thin films: Unravelling the self‐assembly - Hawly, Tim; Streller, Fabian; Johnson, Manuel; Miguez Lago, Sandra; Hammer, Natalie; Hampel, Frank; Vivod, Dustin; Zahn, Dirk; Kivala, Milan; Branscheid, Robert; Spiecker, Erdmann; Fink, Rainer (ChemPhysChem, 2021)
The ability of a series of bridged triarylamines, so‐called N‐heterotriangulenes, to form multilayer‐type 2D‐extended films via a solution‐based processing method was examined using complementary microscopic techniques. We found that the long‐range order, crystallinity, and layer thickness decisively depend on the nature of the substituents attached to the polycyclic backbone. Owing to their flat core unit, compounds exhibiting a carbonyl unit at the bridge position provide a superior building block as compared to thioketone‐bridged derivatives. In addition, nature and length of the peripheral substituents affect the orientation of the aromatic core unit within highly crystalline films. Hence, our results stress the significance of a suitable molecular framework and provide deeper understanding of structure formation in 2D‐confined surroundings for such compounds.<br
Keywords: bridged triarylamines; self-assembly; organic semiconductors; 2D nanomaterials; organic electronics